LOCAL LANGUAGE KEYPAD: KEYBOARD BAHASA DAERAH BERBASIS SMARTPHONE SEBAGAI MEDIA PELESTARIAN BAHASA DAN SASTRA DAERAH - Siti Alvi Sholikhatin; Cindy Magnolia; Reno Dermawan Mutiara Putra (Jurnal RESISTOR (Rekayasa Sistem Komputer), 2021)
The region language and region literature in Indonesia is priceless and must be preserved. Each region has a variety of languages from different groups and become a cultural characteristic of certain region. However, the era of globalization and the development of information technology threatens the existence and preservation of regional languages which is prone to be replaced. The lowering number of speakers and the invasion of foreign languages are the main indicators of the deterioration of the existence of regional languages and literature. One of the efforts to restore the passion of regional language and regional literature is to develop a regional language keyboard that is easy to use by users of all age. The main purpose of the development of regional language keyboards is to introduce regional languages, especially to the younger generation who are beginning to be exposed to globalization so that they tend to forget the language and literature of the region. The keyboard is built with a natural language processing and smartphone-based approach. The Technology Preparedness Level (TKT) is at level 6, which means a demonstration of a model or prototype of a system or subsystem in a relevant environment.